1999
DOI: 10.1046/j.1439-0396.1999.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute deficiency of dietary proline on proline balance in the rat small intestine and liver

Abstract: Introduction  Proline is widely found in all types of mammalian tissue, and accounts for about 20% of the amino acids that constitute collagen (A dams 1970). Proline is nutritionally nonessential but biologically it is an important amino acid and consequently mammalian organisms synthesize the required amounts of proline even in the absence of sufficient proline consumption via food. The metabolism of higher animals is unique, and amino acid metabolism differs from one tissue to the next. Some organs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…While proline and Pycr1 regulation has been linked to Atf4 signalling previously, this was in the context of stem cell differentiation (D'Aniello et al, 2015) and not that of mitochondrial dysfunction. Although it has been suggested that the pancreas is the major site of proline production in vivo (Tran et al, 2021), the kidney has been proposed to operate as a proline-producing organ under conditions of fasting and with low proline diets (Watanabe et al, 1999;Watanabe et al, 1997). Given the high density of mitochondria in proximal kidney tubules, it would be tempting to speculate that high rates of oxidative TCA activity could be important to facilitate proline biosynthesis for use by other organs under conditions of fasting or nutrient scarcity.…”
Section: Discussionmentioning
confidence: 99%
“…While proline and Pycr1 regulation has been linked to Atf4 signalling previously, this was in the context of stem cell differentiation (D'Aniello et al, 2015) and not that of mitochondrial dysfunction. Although it has been suggested that the pancreas is the major site of proline production in vivo (Tran et al, 2021), the kidney has been proposed to operate as a proline-producing organ under conditions of fasting and with low proline diets (Watanabe et al, 1999;Watanabe et al, 1997). Given the high density of mitochondria in proximal kidney tubules, it would be tempting to speculate that high rates of oxidative TCA activity could be important to facilitate proline biosynthesis for use by other organs under conditions of fasting or nutrient scarcity.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the ice plant accumulates proline as compatible solutes in response to osmotic stress (Heun et al, 1981;Demmig and Winter, 1986;Sanada et al, 1995). Proline is a non-essential amino acid involved in the production of collagen (Watanabe et al, 1999) and wound healing, and also is a precursor of hydroxyproline which functions to maintain and heal cartilage, and strengthen joints, tendons, and muscles (Balch and Balch, 2000). Proline and the other compounds described above such as citrate, malate, SOD, and polyols have been produced through industrial processes as commercial supplement tablets from different biological resources.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ability of mammalian cells to synthesize proline, dietary sources of proline are thought to be essential to maintain healthy function (Watanabe et al 1999 ; Yam et al 2019 ). In normal conditions, dietary proteins are hydrolyzed in the small intestine to release proline and hydroxyproline (Fig.…”
Section: Introductionmentioning
confidence: 99%